Evaluation of load-deflection properties of fiber-reinforced composites and its comparison with stainless steel wires - Shiva Alavi; Tayebe Mamavi (Wolters Kluwer Medknow Publications, 2014)
Background: The aim of this study was to evaluate the response of common sized fiber-reinforced composites (FRCs) to different deflections due to bending forces and comparing it with stainless steel (SS) wires. Materials and Methods: In this experimental study, two FRC groups with 0.75 mm and 1.2 mm diameters (Everstick Ortho, Stick Tech, Finland) and three SS groups with 0.016 × 0.022 inch, 0.0215 × 0.028 inch and 0.7 mm diameters (3M Uniteck, Monrovia, California, USA) were tested. Each group contained 10 samples that were tested according to a three point bending test. Each group was tested at deflections of 0.5, 1 and 1.5 mm and the data was analyzed using the repeated measure ANOVA by SPSS software (Statistical Package for the Social Sciences, IBM SPSS, Inc. in Chicago, Illinois, USA). P < 0.05 was considered as significant. Results: The highest recorded load belonged to the 1.2 mm FRC and after that 0.7 mm SS wire, 0.75 mm FRC, 0.0215 × 0.028 inch SS wire and finally 0.016 × 0.022 inch SS wire. The 0.7 mm SS wire and 0.75 mm FRC were compared as retainers and the results showed the 0.7 mm SS wire showed significantly higher load compared with 0.75 mm FRC (P < 0.05). The 1.2 mm FRC had significantly higher load compared to 0.0215 × 0.028 inch and 0.016 × 0.022 inch SS wires (P < 0.05). Conclusion: The results showed that the 1.2 mm FRC group had significantly higher load compared to SS wires and other FRC groups under the 0.5, 1 and 1.5 mm deflections. Therefore, it can be suggested that FRC can be used as an esthetic replacement for SS wires for active and passive purposes in orthodontics.